2017
DOI: 10.1186/s40677-017-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural damage to houses and buildings induced by liquefaction in the 2016 Kumamoto Earthquake, Japan

Abstract: Background: In April 2016, Kumamoto City, Japan, and its surroundings were hit by a sequence of strong and devastating earthquakes including two significant events, one on April 14 th , 2016, at 21:26 JST (Mw6.2) and the other on April 16 th , 2016, at 01:25 JST (Mw7.0). These disasters caused 120 fatalities (including indirect fatalities), 2337 people injured and 177,914 residential houses were damaged. This paper aims to ascertain the damage to residential houses and buildings caused by liquefaction during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Building damage as resulted from earthquake is associated with the geological rock. As a result of the 2016 Kumamoto Earthquake, Japan, most building damage was associated with the liquefaction process (Setiawan et al 2017). Soil liquefaction that occurred in this area after earthquake was mainly affected by the very loose silt and sand layer at a depth of around 6 m below the ground surface, and the existence of the Kiyama river as well.…”
Section: Residential Building Susceptibilitymentioning
confidence: 99%
“…Building damage as resulted from earthquake is associated with the geological rock. As a result of the 2016 Kumamoto Earthquake, Japan, most building damage was associated with the liquefaction process (Setiawan et al 2017). Soil liquefaction that occurred in this area after earthquake was mainly affected by the very loose silt and sand layer at a depth of around 6 m below the ground surface, and the existence of the Kiyama river as well.…”
Section: Residential Building Susceptibilitymentioning
confidence: 99%
“…This will result in substantial losses if this damage occurs on vital roads. Moreover, tilted houses and building also could be appeared due to liquefaction, for instance as happened in Kumamoto earthquake 2016, Japan, where it was reported that many residential houses and buildings were tilted due to liquefaction (Setiawan et al, 2017). The use of gravel and geosynthetics in those examples mentioned above will be able to lower the settlement and the related-damages caused by liquefaction.…”
Section: Vertical Ground Displacementmentioning
confidence: 99%
“…The structural geometry influenced the tilt of the building, its direction, and the foundation used. Besides, the structural self-weight and soil conditions were also factors causing different damage levels to buildings [7]. Lu et al has investigated the impact of liquefaction on lowrise building in the Meinong Earthquake (2015), Taiwan [8], suggesting that the local site effects are essential to be considered.…”
Section: Introductionmentioning
confidence: 99%